Comparison of ASE with in-cell cleanup and the QuEChERS sample preparation methods for the analysis of pesticide residues in tea - Abdul Kadir, Haslina; Abas, Faridah; Mediani, Ahmed; Ismail, Intan Safinar; Lajis, Md. Nordin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The aim of the present work was to compare and choose the best method to extract incurred pesticide residues from green tea. Accelerated solvent extraction (ASE) with in-cell cleanup and the quick, easy, cheap, effective rugged and safe (QuEChERS) methods were tested on green tea samples with incurred beta-endosulfan pesticide. The extracts were analyzed by GC-MS/MS and the recovery and the precision of both methods were compared. The average recovery using ASE with the in-cell cleanup method was in the range of 89 to 92% which is better than that obtained using a QuEChERS method. Both the ASE with in-cell cleanup and the QuEChERS methods provided good precision with RSDs in the range of 12 to 15% and 17 to 18%, respectively. This finding indicates that the ASE method with the in-cell cleanup is more suitable for the accurate determination of pesticides incurred in tea.